The effects of spinal anaesthesia for elective caesarean section on uterine and umbilical arterial pulsatility indexes in normotensive and chronic hypertensive pregnant women: a prospective, longitudinal study - Guedes-Martins, L. (2015)
BACKGROUND: Despite the known effects of neuraxial blockade on major vessel function and the rapid decrease in uterine vascular impedance, it is unclear how the blockade affects the utero-placental circulation in the near-term. We hypothesize that among women with chronic hypertension, a loss of sympathetic tonus consequent to spinal block may cause significant changes in the utero-placental haemodynamics than the changes typical in normal pregnant women. Therefore, the main study objective was to analyse the effect of spinal anaesthesia for caesarean section on uterine and umbilical arterial impedance in pregnant women at term diagnosed with stage-1 chronic hypertension. METHODS: A prospective, longitudinal study was performed in singleton pregnant women (203 low-risk and 33 with hypertension) scheduled to undergo elective caesarean section. The mean arterial blood pressure and pulsatility indexes for the uterine and umbilical arteries were recorded before and after spinal anaesthesia was performed using 8-9 mg hyperbaric bupivacaine (5 mg/mL) and 2-2.5 μg sufentanil (5 μg/mL). Multiple linear regression models with errors capable of correlation or with unequal variances were fitted using the generalized least squares. RESULTS: In normotensive women, the mean arterial blood pressure decreased after administering spinal anaesthesia (p < 0.05). The pulsatility index of the uterine and umbilical arteries did not change after spinal anaesthesia. In the hypertensive women, the mean arterial blood pressure (p < 0.05) and uterine artery pulsatility index (p < 0.05) decreased. In both groups, the umbilical artery pulsatility index did not change after spinal anaesthesia. CONCLUSIONS: In stage-1 chronic hypertensive pregnant women at term, spinal anaesthesia for caesarean section reduces uterine artery impedance but not umbilical artery impedance.